Efektivitas E-Modul Berbasis Problem Based Learningterhadapliterasi Sains Siswa - Supratman Supratman; Wiwi Noviat; Nurul Hidayanti (Peneliti.net, 2023)
This research was motivated by students' lack of scientific literacy, students still did not understand the material being taught, students' test scores on the reproductive system material were still low, learning still used lecture and discussion methods, and the e-modules used were not integrated. So the researchers developed an e-module based on Problem-Based Learning to solve this problem. The purpose of this study is to determine the effectiveness of Problem Based Learning e-modules on students' scientific literacy. This research was conducted in class XI SMAN 1 Alas. The research method was carried out using quasi-experimental research. Based on the results of data analysis using the Paired Sampled T-Test, it was found that the significance value was 0.000. Because the significance value is 0.000 <0.05, it can be concluded that the hypothesis (Ha) is accepted, which means that problem-based learning e-modules on reproductive system material are effective on students' scientific literacy.